Konsumsi Bahan Makanan Sumber Vitamin C dan Kejadian Ketuban Pecah Dini pada Ibu Hamil di Kabupaten Karawang - Irna Trisnawati; Ari Antini (FORIKES, 2022)
Vitamin C is known to play an important role in maintaining the integrity of the membrane that covers the fetus and amniotic fluid. The aim of this study was to determine the effect of consumption of food sources of vitamin C on the incidence of premature rupture of membranes (PROM) in pregnant women. The design of this study was cross-sectional. The research respondents were 102 mothers giving birth in maternity homes and independent midwives in the Karawang Regency area, which were selected by accidental sampling technique. Data were collected through filling out questionnaires and then analyzed using Chi-square test and logistic regression. The results of the analysis showed that the value of p = 0.031 and OR = 2.600. Based on these results, it can be concluded that the consumption of vitamin C has an effect on the incidence of PROM.Keywords: pregnant women; premature rupture of membranes (PROM); vitamin C ABSTRAK Vitamin C diketahui berperan penting dalam mempertahankan keutuhan membran yang menyelimuti janin dan cairan ketuban. Penelitian bertujuan untuk mengetahui pengaruh konsumsi bahan makanan sumber vitamin C terhadap kejadian ketuban pecah dini (KPD) pada ibu hamil. Rancangan penelitian ini adalh cross-sectional. Responden penelitian adalah 102 ibu bersalin di rumah bersalin dan praktik bidan mandiri di wilayah Kabupaten Karawang, yang dipilih dengan teknik accidental sampling. Data dikumpulkan melalui pengisian kuesioner lalu dianalisis menggunakan uji Chi-square dan regresi logistik. Hasil analisis menunjukkan bahwa nilai p = 0,031 dan OR = 2,600. Berdasarkan hasil tersebut dapat disimpulkan bahwa konsumsi vitamin C berpengaruh terhadap kejadian KPD.Kata kunci: ibu hamil; ketuban pecah dini (KPD); vitamin C